Congenital smooth muscle hamartoma. - Garofalo, L. (European Journal of Pediatric Dermatology, 2021)
Smooth muscle hamartoma (SMH) is a localized congenital hyperplasia of the erector pili muscles that becomes less evident over time. Diagnosis is difficult due to its considerable clinical variability. The basic diagnostic criterion is contractility; associated hypertrichosis is the more or less visible clinical sign, that must lead to research contractility. Here was reported an invisible at inspection case, that was diagnosed thanks to the history. In addition, the highly variable clinical aspects of SMH are illustrated and discussed.